2004
DOI: 10.1016/j.phytochem.2004.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Repellency of essential oils of some Kenyan plants against Anopheles gambiae

Abstract: Essential oils of six plants growing in Kenya were screened for repellent activities against Anopheles gambiae sensu stricto. The oils of Conyza newii (Compositeae) and Plectranthus marrubioides (Labiateae) were the most repellent (RD50=8.9 x 10(-5) mg cm(-2), 95% CI) followed by Lippia javanica (Verbenaceae), Lippia ukambensis (Verbenaceae), Tetradenia riparia, (Iboza multiflora) (Labiateae) and Tarchonanthus camphoratus (Compositeae). Eight constituents of the different oils (perillyl alcohol, cis-verbenol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
1
10

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(163 citation statements)
references
References 21 publications
1
151
1
10
Order By: Relevance
“…Although there is broad report on the isolated compounds of T. riparia essential oil, our group still searches for minor constituents that represent a great challenge for researchers. The essential oil of T. riparia present biological activities that are reported in the literature as antispasmodic [4], larvicidal and insecticidal [1], anti-mycobacterial [11], antimalarial [2], repellent of Anopheles gambiae [12], antimicrobial, antinociceptive [8], and acaricidal against Rhipicephalus (Boophilus) microplus [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is broad report on the isolated compounds of T. riparia essential oil, our group still searches for minor constituents that represent a great challenge for researchers. The essential oil of T. riparia present biological activities that are reported in the literature as antispasmodic [4], larvicidal and insecticidal [1], anti-mycobacterial [11], antimalarial [2], repellent of Anopheles gambiae [12], antimicrobial, antinociceptive [8], and acaricidal against Rhipicephalus (Boophilus) microplus [13].…”
Section: Introductionmentioning
confidence: 99%
“…Araujo et al (2012) reported that Piper aduncum essential oil and its principle components (nerolidol, α-humulene and β-caryophyllene) did not show a repellent effect in T. urticae. Conclusive research has shown geraniol to be an effective plant-based mosquito repellent and an insecticide for controlling pests with low mammalian toxicity and biodegradability (Omolo et al, 2004;Chen & Viljoen, 2010). Different concentrations of rose oil and its two important components geraniol and citronellol were found to have contact and repellent effects on T. urticae adult and nymphs and ovicidal effects on eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Traboulsi et al [44] showed that extracts of Foeniculum vulgare leaves were toxic against Culex pipiens larvae, and terpineol and 1,8-cineole were the most effective components in repellency tests. Omolo et al [45] evaluated six plant species growing in the Kenyan coast for repellency on the forearms of human volunteers against Anopheles gambiae. The results showed that some of these constituents from the different oils, such as R-pinene, limonene, 毭-terpinene, and R-terpinene, showed high individual repellencies.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti and An. stephensi mosquitoes (100) were kept in a net cage (45 cm 暳 30 cm 暳 45 cm). The volunteer had no contact with lotions, perfumes, oils or perfumed soaps on the day of the assay.…”
Section: Repellent Activitymentioning
confidence: 99%